Relationship of personal qualities with genetic markers (The Journal of Psychology and Sociology, 2020)
Genetic studies of abilities provide an understanding of the mechanisms that underlie individual dif- ferences in cognitive functions and personality. The predictive nature of psychogenetic studies relates to early findings of genetic markers of personality and cognitive abilities in order to concentrate efforts on goal-directed development. The aim of this article is to investigate the relationship between gene poly- morphisms and personality&intelligence among participants 7-18 years-old who live in Kazakhstan. The first preliminary data of the complex psychometric measurements of intelligence and personality along with molecular-genetic research is presented in this article. Polymorphisms of 50 genes and distributions of their alleles were correlated with verbal and nonverbal intelligence and 14 factors of personality in 27 participants. The results confirm findings previously described in the literature. It is necessary to mention that this is the first genetic study conducted for the local Kazakhstan population. We plan to continue this research to increase sample size for different age groups and include cognitive task performance to study executive control in our experiment.Key words: psychogenetics, gene polymorphism, intelligence, abilities, personality characteristics, test.